ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KONSUMEN DALAM MEMILIH KAFE DI KOTA SURAKARTA - Priyono, Eddy (Benefit: Jurnal Manajemen dan Bisnis, 2006)
Cafee has become an emerging entertainment among urban people at Solo. Therefore, there aremany marketing aspects which interest researcher to study it. Among all those issues, consumer behavioramong cafee consumers becomes the main attention in this study. This study analyses factors relatedwith consumer decision during contacts with service provider (i.e cafee) This research uses regressionanalysis as a tool of analyses. The factors identified in influencing people in choosing cafee areadvertsing, comfortability, live show, date and location. This study gives several suggestion to cafee ownerin Solo to increase their service in order to achieve high income.